Build With Heart for Peoples welfare - Tjoetra, Afrizal (Jurnal Community, 2015)
Typically, the development process set forth in the Medium TermDevelopment Plan (Plan) district / city and province. Derivativedevelopment agenda in the form of a series of programs is reflected in the Budget (APBK) district / city and province. Considering the people asdirect beneficiaries of development, so it will need public participation,both in the planning, implementation and monitoring and evaluation. Ifspace is available and effective consultation in the district / city? Thispaper is intended to arouse stakeholders about the importance of theavailability of space and the public consultation on the regionaldevelopment strategy of the future. According to the theory, thedevelopment process can be criticized conducted through two mainconcepts, namely the modernization theory and dependency theory. Theimportant lesson to be learned from the experience of 10 figures is the first elected regional leaders, for example, and honesty. Secondly, it turns out the area is able to take care of themselves. Third, there must be a rejection of the classical phenomenon of bureaucracy that is corruption, inefficiency, working without vision. Fourth, the intense communication is the key to success, and the fifth is impatient to hear the complaints of the people and work to achieve it